Pengaruh Religiusitas Terhadap Kinerja Karyawan Muslim Kantor Pusat PT. Perkebunan Nusantara XI - Alfisyah, Karina Dewi; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2018)
This study aims to examine the effects of religiousity towards the performance of muslim employees of PT. Perkebunan Nusantara XI Head Office. This study is using quantitive approach. The number of samples in this study are 72 respondents which taken from employees who are Muslims by using simple random sampling technique. This study use questionnaires measured using Likert Scale and analyzed using SPSS 21 program. The results of this study indicate that the religiousity variable has a linear relation with performance variable. Based on the T test, the result shows that the variable religiousity has a significant influence towards the performance variable. Based on the R square test, the result shows that religiousity variable have influence equal to 39,3% to performance variable.